PENCARIAN FILE PADA ANDROID BERBASIS SUFFIX TREE CLUSTERING DENGAN DUKUNGAN WORDNET - Adi Wibowo; Justinus Andjarwirawan; David Valentino (Jurusan Teknik Informatika, 2018)
Finding a specific file in Android devices is not an easy task. Not many apps can search by files’ contents and find terms similarities between user’s queries and files’ terms. This research proposed using Suffix Tree Clustering to index files contents, and WordNet to expand user’s query terms. This research used waterfall as research methodology to built a search engine prototype. There are five steps to index files, i.e. listing and parsing, preprocessing, clustering, merging of clusters, and storing cluster data into database. If a user wants to search files, the prototype will expand user’s query terms using WordNet’s synsets and compare them with clusters stored in a database. The results of this research show that suffix tree clustering and multithreading can be used to index files’ contents, and term expansion can help users to find clusters similar with user’s query terms.